Causal Effects of Sleep Traits on Angina Pectoris: Mediation by Cardiovascular Risk Factors - Zeng C; Ke Y; Li H; Zhang C; Chen J; Chen M (Nature and Science of Sleep)
Chuanfei Zeng,* Yujia Ke,* Huan Li, Chi Zhang, Jian Chen, Mingkai Chen Department of Gastroenterology, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingkai Chen, Email kaimingchen@163.comPurpose: Angina pectoris (AP) is a major factor in heightened risk of cardiac arrest and has been previously linked to sleep patterns. It remains unclear if sleep traits play a role in the onset of AP. Our study aims to declare the causality of sleep traits on AP by Mendelian randomization (MR) analyses.Methods: Genome-wide association study (GWAS) data of sleep traits (sleep duration, insomnia, nap during day, chronotype, getting up in morning, narcolepsy, snoring) were obtained from the UK Biobank. The AP datasets came from an analysis containing samples from the UK biobank, FinnGen, and BioBank Japan. The GWAS data of cardiovascular risk factors (hypertension, smoking, hyperlipidemia, type 2 diabetes mellitus (T2DM)) came from the FinnGen. Two-sample MR analyses were carried out to gain a general map of sleep traits, risk factors and AP, then a multivariable MR was performed and the effect of each factor was calculated.Results: We discovered a positive association between nap, narcolepsy, insomnia and stable angina pectoris (SAP), while getting up in morning associated with SAP negatively. Adequate sleep duration related to a reduced risk of SAP and unstable angina pectoris (UAP). Hypertension and T2DM acted as complete mediators in the relationship of nap and SAP, with an effect value of 1.267 (95% CI = 1.178– 1.363, P < 0.01) and 1.059 (95% CI = 1.000– 1.120, P < 0.05), and the mediating proportion was 27.7% (P < 0.05) and 7.70% (P = 0.102).Conclusion: Our study found that nap, narcolepsy, and insomnia increased the risk of SAP, with hypertension and T2DM mediating the causal relationship between nap and SAP. Getting up in the morning reduced the risk of SAP, while longer sleep duration lowered the risk of SAP and UAP. More evidences are required to clarify the roles of sleep traits and risk factors in AP.Keywords: sleep traits, angina pectoris, hypertension, Mendelian randomization, mediation